2016
DOI: 10.1021/acscatal.6b02642
|View full text |Cite
|
Sign up to set email alerts
|

A Titanium–Organic Framework: Engineering of the Band-Gap Energy for Photocatalytic Property Enhancement

Abstract: A visible-light-responsive metal−organic framework based on titanium hexameric cluster and high conjugation system of organic linker building block termed MOF-902 was synthesized and fully characterized. The photocatalytic properties of MOF-902 were investigated in the polymerization reaction with various monomers such as methyl methacrylate (MMA), benzyl methacrylate (BMA), and styrene (St), respectively. Gel permeation chromatography (GPC) analysis results demonstrated the high performance of MOF-902 as a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(76 citation statements)
references
References 33 publications
(19 reference statements)
2
74
0
Order By: Relevance
“…Ti‐MOFs are especially interesting due to their high stability and photocatalytic activity. However, only a limited number of Ti(IV)‐carboxylate‐based MOFs (MIL‐125 and its derivatives, PCN‐22, COK‐69, MOF‐901, and MOF‐902) have been reported, possibly due to synthetic difficulties. The first Ti‐MOF, MIL‐125, is constructed from [Ti 8 O 8 (OH) 4 (COO) 12 ] clusters and BDC linkers ( Figure ).…”
Section: Stable Metal–organic Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Ti‐MOFs are especially interesting due to their high stability and photocatalytic activity. However, only a limited number of Ti(IV)‐carboxylate‐based MOFs (MIL‐125 and its derivatives, PCN‐22, COK‐69, MOF‐901, and MOF‐902) have been reported, possibly due to synthetic difficulties. The first Ti‐MOF, MIL‐125, is constructed from [Ti 8 O 8 (OH) 4 (COO) 12 ] clusters and BDC linkers ( Figure ).…”
Section: Stable Metal–organic Frameworkmentioning
confidence: 99%
“…MOF‐901 and MOF‐902 are a class of unique MOFs as they combine the synthetic strategies of MOFs and covalent–organic frameworks . A hexameric Ti‐oxo‐cluster, [Ti 6 O 6 (OMe) 6 (ABZ) 6 ] (ABZ = 4‐aminobenzoate), was in situ generated which was further extended into a 2D layer through an imine condensation reaction between amino groups and dialdehyde spacers ( Figure ).…”
Section: Stable Metal–organic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…However,t he documented Ti CPs or the so-called Ti metal-organic frameworks (TiM OFs) thus far are still relatively rare. [21][22][23][24][25][26][27] In fact, due to the high reactivity of the commonly employed Ti precursors, the controllable synthesiso f multidimensional Ti CPs is still challenging. Therefore, to develop as imple, universal synthetic strategy of Ti CPs is particularly necessary.…”
Section: Introductionmentioning
confidence: 99%
“…15). This is an important control experiment as smaller-sized crystals typically offer higher catalytic activity if the catalysis is taking place on the external surface 26 . Since there was little change in polyMMA yield when using different sized particles of MOF-907, it is effectively concluded that the reaction took place mostly within the pores as a result of the unique structural features of MOF-907 26 .…”
Section: Resultsmentioning
confidence: 99%